GAZE STABILITY EXERCISE DAN SENAM THAI CHI BERPENGARUH TERHADAP KESEIMBANGAN LANSIA - Adenikheir, Annisa; Syah, Irhas (PHYSIO MOVE JOURNAL, 2022)
Abstract : Dynamic balance is the ability of people to move from one point or space to another by maintaining balance. Balance is a complex interaction of sensory systems (vestibular, visual, and somatosensory including propioceptors) and musculoskeletal (muscles, joints and other soft tissues) that are modified or regulated in the brain in response to changes in external and internal conditions. The purpose of this study was to determine The Effect of Gaze Stability Exercise and Thai Chi Gymnastics on Elderly Women on Increasing Dynamic Balance at JorongSimpang AA in 2020. It was Quasi-experimental design by using two groups pre and posttest design. The population was 20 respondents in 2020. By using purposive sampling technique, 10 samples were obtained. The data was collected by measuring before and after the intervention. The data was analyzed by computerization by using the Mann Whitney test. The results showed that the average dynamic balance of elderly women after giving Thai Chi Gymnastics was 30.6 and the average dynamic balance of elderly women after giving Gaze Stability Exercise and Thai Chi Gymnastics was 33.4. The results of statistical analysis showed that there were significant differences for the two groups with P value of 0.005 after 10 interventions. It can be concluded that giving Gaze Stability Exercise and Thai Gymnastics has an effect on increasing dynamic balance in elderly women in Jorong Simpang AA with an age range of 60-74 years.  ABSTRAK : Keseimbangan dinamis adalah kemampuan orang untuk bergerak dari satu titik atau ruang ke lain titik dengan mempertahankan keseimbangan. Keseimbangan merupakan interaksi yang kompleks dan integrasi atau interaksi sistem sensorik dan muskuloskeletal (otot, sendi dan jaringan lunak lain) yang dimodifikasi atau di atur dalam otak sebagai respon terhadap perubahan kondisi ekternal dan internal. Tujuan dari penelitian ini untuk mengetahui Pengaruh Gaze Stability Exercise dan senam Thai Chi pada lansia perempuan terhadap peningkatan keseimbangan dinamis. Jenis penelitian ini adalah Quasi-eksperimen dengan menggunakan rancangan one group pre dan post test design. Pengambilan sempel pada penelitian menggunakan teknik Purposive Sampling sehingga didapatkan sempel sebanyak 10 orang. Pengumpulan data dengan cara perlakuan yang di ukur sebelum dan sesudah pemberian intervensi. Pengolahan data hasil penelitian dilakukan secara komputerasi menggunakan uji Mann Whitney.  Hasil penelitian menunjukkan bahwa Rata-rata keseimbangan dinamis lansia perempuan setelah pemberian Gaze Stability Exercise Dan Senam Thai Chi adalah 33,4. Hasil analisis statistic menujukkan terdapat perbedaan signifikan dengan Hasil P Value sebesar 0,005. Dapat disimpulkan bahwa pemberian Gaze Stability Exercise Dan Senam Thai berpengaruh untuk meningkatkan keseimbangan dinamis pada lansia perempuan di Jorong Simpang AA dengan rentang usia 60-74 tahun.Kata Kunci  : Keseimbangan Dinamis, Gaze Stability Exercise, Senam Thai Chi